ChemInform Abstract: ThPt2: A new Representative of Close Packed Tetragonal Structures. Issue 36 (September 2015) - Gumeniuk, Roman; Schnelle, Walter; Burkhardt, Ulrich; Borrmann, Horst; Nicklas, Michael; Ormeci, Alim; Kohout, Miroslav; Leithe‐Jasper, Andreas; Grin, Yuri
Abstract The crystal and electronic structure, chemical bonding, and physical properties of ThPt2 are characterized by powder XRD, magnetic, electrical resistivity and specific heat measurements, and by DFT scalar‐relativistic electronic structure calculations.